Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation. Issue 1 (December 2017) - Muschitiello, Francesco; Pausata, Francesco; Lea, James; Mair, Douglas; Wohlfarth, Barbara
Abstract Volcanic eruptions can impact the mass balance of ice sheets through changes in climate and the radiative properties of the ice. Yet, empirical evidence highlighting the sensitivity of ancient ice sheets to volcanism is scarce. Here we present an exceptionally well-dated annual glacial varve chronology recording the melting history of the Fennoscandian Ice Sheet at the end of the last deglaciation (∼13, 200–12, 000 years ago). Our data indicate that abrupt ice melting events coincide with volcanogenic aerosol emissions recorded in Greenland ice cores. We suggest that enhanced ice sheet runoff is primarily associated with albedo effects due to deposition of ash sourced from high-latitude volcanic eruptions. Climate and snowpack mass-balance simulations show evidence for enhanced ice sheet runoff under volcanically forced conditions despite atmospheric cooling. The sensitivity of past ice sheets to volcanic ashfall highlights the need for an accurate coupling between atmosphere and ice sheet components in climate models. The impact of volcanism on ice sheet melting during the last deglaciation is poorly understood and limited by a lack of suitable proxies. Here, the authors combine annually resolved records of ice sheet melting with numerical models to show that ice sheets are sensitive to high-latitude volcanic eruptions.